IS THE PRESENT ORGANIZATIONAL CULTURE OF HUNGARIAN COMPANIES AFFECTED BY THEIR PAST STATE OWNERSHIP - Jarjabka, Akos (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examines empirically how culturally rooted behavior forms can be detected in Hungarian organizations that were state-owned before the transition. A hypothesis is established and tested through the statistical analysis of a questionnaire-based survey conducted at the Faculty of Business and Economics, University of Pecs, Hungary. The original hypothesis is confirmed by the results of the analysis.